The influence of self‐management, anxiety and depression on chronic eczema‐related quality of life. Issue 4 (7th March 2022) - Standen, Laura; Garip, Gulcan
Abstract: Chronic eczema, a persistent inflammatory skin condition, affects 1 in 12 adults in the United Kingdom and negatively influences quality of life. Self‐management can potentially influence chronic conditions, such as eczema, reducing symptoms and positively influencing quality of life; however, there is a lack of public education for eczema. Anxiety and depression negatively influence quality of life, and frequently present alongside eczema. Psychological interventions for anxiety and depression have shown to be effective for eczema‐related quality of life. This study aimed at examining the relationship between self‐management, anxiety, and depression, on quality of life in individuals with chronic eczema. The main hypothesis proposed that anxiety and depression reduce the influence of eczema self‐management on quality of life, potentially as individuals might be less likely to support their eczema treatment when experiencing symptoms of anxiety and depression. A cross‐sectional design and opportunistic sampling were used to analyse the data from 77 participants who responded to four self‐report scales to assess self‐management understanding, anxiety, depression and quality of life in participants with chronic eczema. Data were analysed by a hierarchical multiple linear regression to assess the variance contributed by each variable added to the model. Results from this sample shows a trend whereby self‐management of eczema contributes less variance to quality of life alongside comorbid anxiety and depression; this suggests that self‐management has reduced influence on eczema‐related quality of life when anxiety and depression are present. Furthermore, low self‐management, high anxiety, and high depression significantly negatively influence quality of life. The three variables combined accounted for 41.1% of variance in quality of life scores, suggesting anxiety, depression and self‐management influence quality of life in the sample. Self‐management, anxiety, and depression significantly influence eczema‐related quality of life, and participants who reported comorbid anxiety and depression were more likely to report lower levels of self‐management in this sample.